EKSTRAK TUMBUHAN SEBAGAI INSEKTISIDA BOTANI UNTUK PENGENDALIAN ULAT GRAYAK JAGUNG SPODOPTERA FRUGIPERDA J. E. SMITH - Burhanuddin Haji Nasir; Nur Khasanah; Idham Idham; Mohammad Yunus; Moh. Hibban Toana; Usman Made (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
Maize is an important commodity after rice that gets priority in increasing food security in Indonesia. The emergence of Invasive Spodoptera frugiperda pests in Indonesia is a threat to the sustainability of maize production in Central Sulawesi. The use of synthetic insecticides to control these pests has various negative impacts. To reduce the negative impact, botanical insecticides can be used. The problem in the use of botanical insecticides is that farmers do not know the effective plant extract control S. Fugiperda. The community service program aims to accompany farmers to develop the extract of Calotropic gigantea, Vitex negundo, and Ageratum conyzoides. Implementation method with the participatory action program approach with stages: counseling and training, technology design, extract application demonstration, observation of S. frugiperda attack intensity, and community assistance. The results show that farmers can make and apply plant extracts C. gigantea, V. negundo and A. conyzoides. The three types of plant extracts can suppress the intensity of S. frugiperda attacks. Extract C. gigantea suppresses S. fugiperda attacks (6.71% to 4.04% on 35 HST, and 3.35% to 1.7% on 42 HST), Extract V. negundo (6.71% to 4, 62% and 3.35% to 2.43%) and extract A. conyzoides (6.71% to 4.99% and 3.35% to 2.43%). Thus, the three types of plant extracts have the potential as effective botanical pesticides to control S. frugiperda